2021
DOI: 10.3389/fonc.2021.762444
|View full text |Cite
|
Sign up to set email alerts
|

Myosteatosis Differentially Affects the Prognosis of Non-Metastatic Colon and Rectal Cancer Patients: An Exploratory Study

Abstract: Body composition performed by computed tomography (CT) impacts on cancer patients’ prognoses and responses to treatment. Myosteatosis has been related to overall survival (OS) and disease-specific survival in colorectal cancer (CRC); however, the independent impact of the association of myosteatosis with prognosis in colon cancer (CC) and rectal cancer (RC) is still unclear. CT was performed at the L3 level to assess body composition features in 227 patients with CRC. Clinical parameters were collected. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…It's noteworthy that the disparities observed in our study may have diverse impacts on prognosis. Supporting this hypothesis, previous research demonstrated that myosteatosis influenced the survival in patients with colon cancer but not in those with rectal cancer 19 , emphasizing the need to differentiate between the two when analyzing BC.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It's noteworthy that the disparities observed in our study may have diverse impacts on prognosis. Supporting this hypothesis, previous research demonstrated that myosteatosis influenced the survival in patients with colon cancer but not in those with rectal cancer 19 , emphasizing the need to differentiate between the two when analyzing BC.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, we found that 68.7% of patients with CRC had low SMD. Furthermore, a low SMD also points to worse general and CRC-specific mortality than those with a normal SMD 19,20,29 . It's noteworthy that the disparities observed in our study may have diverse impacts on prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The software was used to quantify the skeletal muscle and adipose tissue content at the third lumbar vertebra level to evaluate sarcopenia and myosteatosis according to previously established parameters (15). Different specific Hounsfield unit (HU) thresholds were assigned for various tissues: -29 to +150 HU for skeletal muscle, -150 to -50 HU for visceral adipose tissue, and -190 to -30 HU for subcutaneous and intramuscular adipose tissue (16).…”
Section: Body Composition Analysis Based On Ctmentioning
confidence: 99%
“…The system parameters were calibrated with Houns eld unit (HU) attenuation values as follows: -190 to -30 HU for subcutaneous and intramuscular adipose tissue, -150 to 50 HU for visceral adipose tissue, and − 29 to + 150 HU for skeletal muscle (Fig. 1) [21]. The diagnostic parameters were formulated based on the patient's BMI: for patients with a BMI ≥ 25 kg/m², an SMI < 53 signi ed sarcopenia, and an SMA < 33 HU signi ed myosteatosis.…”
Section: Body Composition Analysis Via Ctmentioning
confidence: 99%